Phylum Cnidaria - Deserti, María Irene; Grohmann, Priscila A.; Stampar, Sérgio N. [UNESP] (Elsevier, 2020)
This chapter offers a summary of freshwater cnidarians from the Neotropical region. A short review on methods of identification with the most relevant aspects of morphology and biology can be found, as well as a key identification based on the most recent studies of the group. In this chapter you will find the basic tools necessary to be able to take your first steps in the study of these fascinating animals.
Keywords: Cnidae; Cnidaria; Freshwater; Hydra; Hydrozoa; Jellyfish